More than insulator: multiple roles of CTCF at the H19-Igf2 imprinted domain - Singh, Purnima; Lee, Dong-Hoon; Szabo, Piroska E. (Frontiers in Genetics, 2012)
CTCF-mediated insulation at the H19-Igf2 imprinted domain is a classic example for imprinted gene regulation. DNA methylation difference in the imprinting control region (ICR) is inherited from the gametes and subsequently determines parental allele-specific enhancer blocking and imprinted expression in the soma. Recent genetic studies showed that proper monoallelic enhancer blocking at the H19-Igf2 ICR is critical for development. Strict biallelic insulation at this locus causes perinatal lethality, whereas leaky biallelic insulation results in smaller size but no lethality. Apart from enhancer blocking, CTCF is also the master organizer of chromatin composition in the maternal allele along this imprinted domain, affecting not only histone tail covalent modifications but also those in the histone core. Additionally, CTCF binding in the soma protects the maternal allele from de novo DNA methylation. CTCF binding is not involved in the establishment of the gametic marks at the ICR, but it slightly delays de novo methylation in the maternally inherited ICR allele in prospermatogonia. This review focuses on the developmental and epigenetic consequences of CTCF binding at the H19-Igf2 ICR.